Cardiovascular Risk Factors after Childhood Cancer Treatment Are Independent of the FTO Gene Polymorphism? - Małgorzata Sawicka-Żukowska; Maryna Krawczuk-Rybak; Paweł Bernatowicz; Katarzyna Muszyńska-Rosłan; Jerzy Konstantynowicz; Włodzimierz Łuczyński (International Journal of Endocrinology)
The study objective was to assess the prevalence of cardiovascular disease risk factors in patients treated for childhood cancer (N=101) and to determine the involvement of clinical (cancer type and therapy) and/or genetic (FTO gene rs9939609 polymorphism) factors. Anthropometric features, laboratory findings, and standardized osteodensitometric indices (fat and lean mass) were considered. Overweight/obesity was found in 17.82% of the patients; however, central adiposity was found in as many as 42.5%. At least one abnormality in lipid metabolism was observed in 35.6%. Densitometry revealed elevated levels of fat mass in 44.55% of the patients. None of the parameters studied were associated with the FTO gene polymorphism. Standardized waist circumference was significantly higher in patients treated for leukemia than those treated for solid tumors (p=0.04). Our findings indicate a high rate of central adiposity among childhood cancer survivors, especially leukemia patients. The prevalence of risk factors of cardiovascular disease after anticancer therapy is not FTO gene polymorphism-dependent.